2015
DOI: 10.1371/journal.pone.0127087
|View full text |Cite
|
Sign up to set email alerts
|

Impaired M. tuberculosis Antigen-Specific IFN-γ Response without IL-17 Enhancement in Patients with Severe Cavitary Pulmonary Tuberculosis

Abstract: BackgroundTh1 cells play an essential role in immune protection against tuberculosis. Th17 cells might be involved with immune pathology in active human tuberculosis (TB). The balance between Th1 and Th17 cells in patients with cavitary tuberculosis needs to be clarified which might help understanding the immunological basis of pathologic pathogenesis in TB.MethodInitially treated pulmonary TB (PTB) patients with or without cavities were recruited before chemotherapy. We isolated peripheral blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Previous studies have indicated that Mtb -specific CD4 T-cell responses differ between TBP and subjects with LTBI, although data on the character of the differences are not uniform ( 18 22 ). To immunologically characterize TBP included in our study, we compared Th1 responses in TBP, individuals with LTBI, TBC, and HD groups.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that Mtb -specific CD4 T-cell responses differ between TBP and subjects with LTBI, although data on the character of the differences are not uniform ( 18 22 ). To immunologically characterize TBP included in our study, we compared Th1 responses in TBP, individuals with LTBI, TBC, and HD groups.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were included in the study according to the following criteria: (1) diagnosed as newly treated active PTB confirmed by bacteriology with all information regarding bacteriology or pathology, and typical radiological manifestation; (2) patients with severe cavitary PTB with at least one large cavity of ≥3 cm in diameter or at least three cavities regardless of the diameter of cavities or patients with mild lesion PTB without a cavity (patients had mild lesions in ≤two lung fields and no cavity) as reported previously [3], a cavity, or non-cavitary lesions in lungs, which could be observed in a chest computed tomography (CT) scan; (3) patients had never been treated for TB or the anti-TB treatment duration was within 1 week; (4) subjects provided informed consent for the study. During the same period, healthy volunteers were recruited for the control group.…”
Section: Methodsmentioning
confidence: 99%
“…TB cases and tuberculin skin test-positive healthy donors have variant immune responses to MTB ( Mycobacterium tuberculosis ) antigens [23]. A large variation has been observed in immune responses of patients with differing severities of active pulmonary tuberculosis (PTB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, there were 9 million new cases of TB diagnosed and 1.5 million deaths due to the disease [ 1 ]. Adaptive immune responses mediated by CD4 + T cells and CD8 + T cells, and T helper (Th) 1 cytokines characterized by interferon (IFN)-γ production are associated with a good prognosis and play an important role in countering the progression of MTB infection [ 2 4 ]. However, Th1 cells (primarily CD4 + cells producing IFN-γ) alone are not capable of controlling the infection [ 3 , 5 ] and other factors, including Th2 cells, Th17 cells and regulatory T cells (Treg cells), are also involved in the progression of MTB infection.…”
Section: Introductionmentioning
confidence: 99%